Difference in abiotic and biotic parameters between old growth forest and oil palm plantation - Mathavan Vickneswaran (2018)
Old growth forests (OG) are forest type that is in a late successional condition and free of evidence of human activity. Sabah's old growth forests are biodiversity hotspot that is extant its tropical rainforest. However, old growth forest is drastically being replaced by the agricultural plantation. Since the 1970s, oil palm plantation (OP) in Sabah has expanded to 17% of Sabah's land cover. However, such rapid conversion is poorly characterized as few research is done to explore the impacts of land conversion on changes in soil physical and chemical parameters, and how it influences the distribution of soil fauna community. Soil samples were collected from geographically similar plots from two different land-use types, OG and OP plantation, at 0-30 cm soil depth and were characterised based on layers. Analysis of soil parameters had shown that forest conversion had increased bulk density, pH, dissolved nitrogen and microbial biomass nitrogen, significantly (p<0.05). Further, multivariate modeling indicates that dissolved nitrogen and organic matter percentage to be the most discriminating soil parameter between the land-uses. Microbial biomass carbon was recorded to be lower in OP plantation (0.56 mg/g) compared to OG (0. 79 mg/g). However, additionally bacterial communities revealed that OP soil has a more diverse bacterial community. Organic mineral layer of OP had recorded staggering 60.1 % of unshared OTUs compared to OG with 47.5%. In fact, there is increase of OP unshared OTUs, from 57.4% to 60.1 %. Oil palm recorded staggering 49.2% of unshared OTUs in the organic layer and 50. 9% in the organicmineral layer, compared with old growth forest only recorded 48.6% and 33.9% for both organic and organic-mineral layer. Data of litterfall arthropods showed a total of 2722 individual of litterfall arthropod with 17 orders was found in old growth forest, meanwhile only 849 individuals with 14 orders were found in the plantation. Based on relationship analysis output, it is noted that order Collembola has high toleration toward soil with a high concentration of labile carbon. Meanwhile, order Hymenoptera is observed to be abundant in soil plot with high organic matter percentage and phenolic concentration. In conclusion, our findings suggest that old growth forest conversion to oil palm plantation causes alterations to the biotic and abiotic factors, making both land-use of being totally distinctive from each other.